A framework for spillover effect of corporate social responsibility with a case study of Chinese dairy industry. (2016) - Zhang, Haixin; Zhang, Mengying; Ding, Donghong; Liu, Hongwei
The spillover effect of corporate social responsibility gets little attention from researchers. We articulate a research framework for studying the spillover effect of CSR and discuss some essential research issues including the existence and classification of spillover effect, influential factors of spillover effect, the dominance spillover effect and managerial strategies. The discussion results propose useful implication for further empirical research. Furthermore, we operate a case study. By using Sharpe's one-way analysis of variance to estimate the cumulative abnormal return of stocks, the paper expands the research on contagion effect and contrast effect which are two kinds of spillover effect. The results partially support the research framework, provide us some qualitative understanding of spillover effect and propose some managerial implications.